Nurses' knowledge, concerns, perceived impact and preparedness toward COVID‐19 pandemic: A cross‐sectional survey. Issue 6 (30th September 2021) - El‐Monshed, Ahmed Hashem; Amr, Mostafa; Ali, Ahmed Salah; Elmasry, Yosr Mohamed; Zoromba, Mohamed
Abstract: Aim: This study aimed to assess the nurses' knowledge, concerns, perceived impact and preparedness toward the COVID‐19 pandemic. Background: As COVID‐19 is a new disease, its spread and emergence cause fear, anxiety and confusion among the general population. Nurses are in close contact with infected persons, and their knowledge plays an important role in preventing the transmission chain. Methods: In this cross‐sectional study, 207 nurses were selected using convenience sampling from 29 March to 19 April 2020. The study used a questionnaire assessing the nurses' baseline characteristics, their source of information, knowledge, concerns, the perceived impact and their preparedness for the COVID‐19 pandemic. Results: Around half of the surveyed nurses (51.2%) reported that the Ministry of Health's and World Health Organization's websites and official pages were their main sources of information. The majority of nurses (81.6%) knew the nature of the virus, 83.6% agreed that their job puts them at risk of infection with COVID‐19 and 72% felt personally prepared for the pandemic. Conclusion: The majority of nurses had an acceptable level of knowledge regarding COVID‐19. However, psychological interventions are needed to be addressed in the planning stage before any pandemic. Summary statement: What is already known about this topic? It is well established that COVID‐19 is a highly infectious disease with a fatality rate of about 6.48% in Egypt. Studies about nursing and COVID‐19 are relatively few. There is a lack of data regarding the nurses' knowledge, concerns, perceived impact and preparedness toward COVID‐19. What does this paper add? Nurses prefer gaining their knowledge regarding COVID‐19 from the Ministry of Health's and the World Health Organization's websites and official pages rather than the social media websites. Nurses have an acceptable level of knowledge regarding COVID‐19. The majority of surveyed nurses knew the nature of the virus along with its signs and symptoms. The majority of surveyed nurses feel that their job puts them at the risk of infection with COVID‐19, and they are quite afraid of being infected. The implications of this paper: Psychological interventions are needed in the planning stage before any pandemic to enhance the protection of nurses and health care workers and to reduce the psychological impact. Sustainable awareness programmes are required for health care workers, keeping them up to date with the most recent information regarding prevention and management methods from the World Health Organization's guidelines and other instructional materials. Hospitals can hold meetings and organize regular psychological support groups to allow nurses to manage their fears and acquire stress reduction strategies.